221k views
0 votes
75 – 3.5y – 4y = 4y + 6

1 Answer

5 votes

Simplifying

75 + -3.5y + -4y = 4y + 6

Combine like terms: -3.5y + -4y = -7.5y

75 + -7.5y = 4y + 6

Reorder the terms:

75 + -7.5y = 6 + 4y

Solving

75 + -7.5y = 6 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.

75 + -7.5y + -4y = 6 + 4y + -4y

Combine like terms: -7.5y + -4y = -11.5y

75 + -11.5y = 6 + 4y + -4y

Combine like terms: 4y + -4y = 0

75 + -11.5y = 6 + 0

75 + -11.5y = 6

Add '-75' to each side of the equation.

75 + -75 + -11.5y = 6 + -75

Combine like terms: 75 + -75 = 0

0 + -11.5y = 6 + -75

-11.5y = 6 + -75

Combine like terms: 6 + -75 = -69

-11.5y = -69

Divide each side by '-11.5'.

y = 6

User Cafonso
by
6.3k points